2016
DOI: 10.1371/journal.pone.0161651
|View full text |Cite
|
Sign up to set email alerts
|

Association of MicroRNAs with Antibody Response to Mycoplasma bovis in Beef Cattle

Abstract: The objective of this study was to identify microRNAs associated with a serum antibody response to Mycoplasma bovis in beef cattle. Serum from sixteen beef calves was collected at three points: in summer after calves were born, in fall at weaning, and in the following spring. All sera collected in the summer were ELISA-negative for anti-M. bovis. By the fall, eight animals were seropositive for IgG (positive group), while eight remained negative (negative group). By spring, all animals in both groups were sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, analysis of biobanked bovine serum samples from experimental infections with MAP (stored at −20°C for 10–15 years) revealed that the circulating miRNA profile was remarkably similar in composition to the profile from fresh sera (<1 year at −80°C) ( 94 ). miRNAs have also been shown to correlate with season (summer, after the calves were born; fall, at weaning; and the following spring) when serum from Mycoplasma bovis -infected calves was profiled, but similar to the MAP studies described above a strong signature of infection was not observed ( 224 ).…”
Section: Differential Expression Of Circulating Mirnas In Specific Inmentioning
confidence: 79%
“…On the other hand, analysis of biobanked bovine serum samples from experimental infections with MAP (stored at −20°C for 10–15 years) revealed that the circulating miRNA profile was remarkably similar in composition to the profile from fresh sera (<1 year at −80°C) ( 94 ). miRNAs have also been shown to correlate with season (summer, after the calves were born; fall, at weaning; and the following spring) when serum from Mycoplasma bovis -infected calves was profiled, but similar to the MAP studies described above a strong signature of infection was not observed ( 224 ).…”
Section: Differential Expression Of Circulating Mirnas In Specific Inmentioning
confidence: 79%
“…bovis compared to seronegative controls (Casas et al . ). The identification of leading‐edge genes in the regulatory RNA gene set suggests that dysregulation of microRNAs affects susceptibility to BRD through a diminished innate and adaptive immune response during BRD infection.…”
Section: Resultsmentioning
confidence: 97%
“…In the initial characterization of the host transcriptional responses in five tissues following intratracheal M. bovis administration, differential expression of 157–994 genes was detected (depending on tissue), with the BPIFA1 , C9 and CD14 genes identified as “key players” in the immune function networks (Behura et al., ). In addition, recent analysis of microRNAs circulating in sera from beef cattle that had been naturally or experimentally infected with M. bovis has identified four microRNAs (bta‐let‐7b, bta‐miR‐24‐3p, bta‐miR‐92a and 423‐5p) that are associated with a humoral antibody response (Casas et al., ). Each of these molecules had been previously shown to be involved in the immune response of dairy cattle to bacterial infection.…”
Section: Gap Analysismentioning
confidence: 99%